Influence of the dispersant on the parts quality in slurry‐based binder jetting of SiC ceramics. Issue 12 (21st August 2022) - Diener, Sarah; Schubert, Hendrik; Held, Alexander; Katsikis, Nikolaos; Günster, Jens; Zocca, Andrea
Abstract: Binder jetting is establishing more and more in the ceramic industry to produce large complex shaped parts. A parameter with a great impact on the quality of the parts is the binder–powder interaction. The use of ceramic slurries as feedstock for this process, such as in the layerwise slurry deposition–print technology, allows a great flexibility in the composition. Such slurries are typically composed of ceramic powder, water, and small amounts of various additives. The understanding of the effect of these components on the printing quality is thus essential for the feedstock development. Four models were developed regarding the impact of additives, such as dispersants on printing. These models were confirmed or rebutted by experiments performed for an SiC slurry system with two different concentrations of a dispersant and a commercial phenolic resin used as a binder. It is shown that for this system the influence of the dispersant on the curing behavior and the clogging of the pores by dispersant can be neglected. The redispersion of the dispersant after the curing of the resin has no or only a minor effect. However, the wetting behavior determined by the surface energies of the system seem to be most crucial. In case the surface energy of the slurry additive is significantly lower than the surface energy of the binder, the strength of the green parts and the printing quality will be low. This was shown by inverse gas chromatography, contact angle measurement, rheological characterization, and mechanical tests with casted samples. Abstract :